2018
DOI: 10.1016/j.actbio.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Customizing poly(lactic-co-glycolic acid) particles for biomedical applications

Abstract: Nanoparticles are increasingly important in the field of biomedicine. Particles made of polymers are in the spotlight, due to their biodegradability, biocompatibility, versatility. In this review, we aim to discuss the range of formulation techniques, manipulations, and applications of poly(lactic-co-glycolic acid) (PLGA) particles, to enable a researcher to effectively select or design the optimal particles for their application. We describe the various techniques of PLGA particle synthesis and their impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
195
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(204 citation statements)
references
References 124 publications
1
195
0
1
Order By: Relevance
“…While many of these delivery systems have been reviewed elsewhere [80], efforts have focused on developing NPs from poly(lactic-co-glycolic acid) (PLGA), a biocompatible and biodegradable polymer, well-known to the FDA [81]. In addition to their favorable safety profiles [82,83], drug release from PLGA NPs is highly tunable by adjusting polymer molecular weight and ratio of lactic to glycolic acid [84]. Recently, Mandl et al showed that NP size can be tuned to alter biodistribution and accumulation of NPs in sites of interest, such bone marrow or lung [85].…”
Section: Plga Nanoparticle-mediated Delivery Of Pnasmentioning
confidence: 99%
“…While many of these delivery systems have been reviewed elsewhere [80], efforts have focused on developing NPs from poly(lactic-co-glycolic acid) (PLGA), a biocompatible and biodegradable polymer, well-known to the FDA [81]. In addition to their favorable safety profiles [82,83], drug release from PLGA NPs is highly tunable by adjusting polymer molecular weight and ratio of lactic to glycolic acid [84]. Recently, Mandl et al showed that NP size can be tuned to alter biodistribution and accumulation of NPs in sites of interest, such bone marrow or lung [85].…”
Section: Plga Nanoparticle-mediated Delivery Of Pnasmentioning
confidence: 99%
“…Poly(lactide‐coglycolic acid) (PLGA) nanoparticle (NP) has been widely used in the field of nanomedicine due to its excellent biocompatibility and biodegradability. [ 1 ] It also favors the clinical translation since PLGA was approved by the US Food and Drug Administration (FDA). [ 2 ] Recently, the chemotherapeutic drug and photosensitizer coloaded PLGA NPs have emerged as a promising combined chemo‐photothermal therapy in the malignant cancer due to their synergistic antitumor effect and reduced tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles serve as a suitable platform to develop such localized interventions since they have been used to package and deliver diverse therapeutic agents. In particular, the polymer poly (lactic-co-glycolic acid) (PLGA), which has excellent biocompatibility and biodegradability, has been U.S. Food and Drug Administration (FDA) approved and extensively used to deliver synergistic drug combinations [2][3][4][5]. These properties make PLGA an excellent candidate for applications involving the controlled release of encapsulated agents and improved drug pharmacokinetics in vivo [6,7].…”
Section: Introductionmentioning
confidence: 99%